Combining HFEPR and NMR spectroscopies to characterize organochromium(III) complexes with large zero-field splitting - Krzystek, Jurek; Kohl, Gerald; Hansen, Helge-Boj; Enders, Markus; Telser, Joshua (Organometallics, 2019)
A series of three organochromium(III) complexes, based on a quinoline-substituted cyclopentadienyl ring coordinated to a CrCl2 moiety—C5Me4(C9NH6)CrCl2 (1), C5Ph4(C9NH6)CrCl2 (2), and C5Me4(C11NH10)CrCl2 (3)—has been investigated by EPR spectroscopy, including high-frequency and -field EPR (HFEPR) as well as by 1H NMR. Complex 3 is new and has higher solubility than 1 and 2, which could potentially improve its activity as an alkene polymerization precatalyst, an application that has already been documented for 1 and 2. The HFEPR studies show that 1-3 exhibit zero-field splitting (zfs) that is unusually large for Cr(III) (3d3, S = 3/2), as given by the axial zfs parameter D ≥ ∼3 cm-1. The zfs determined here for 1 is in good agreement with previous theoretical studies of this complex by other workers, which were made in the absence of any knowledge of the experimental data. Such a “blind” comparison of theory and experiment is very rare. The NMR spectra of 3 are fully analyzed using the zfs data and clearly show the dominant contribution of Fermi contact shifts, now that the pseudocontact (dipolar) shifts can be accurately determined. The results show the power of integrated magnetic resonance (EPR and NMR) spectroscopy combined with theoretical calculations in understanding the subtleties of electronic structure of the paramagnetic organometallic complex, in this case with S > 1/2, which could then be related to chemical reactivity or magnetic properties.
Gesehen am 18.12.2019